Note on Same Amazing properties of Perfect Numbers - Mulatu, Lemma; Kayla Jones (IJRDO -JOURNAL OF MATHEMATICS, 2020)
Number theory has been a fascinating topic for many mathematicians because of the relationships they can find between numbers and their divisors. One of which are, perfect numbers. They date back to ancient Greek mathematics when they studied the relationships between numbers and their divisors. As of 2018, there are currently 50 perfect numbers that have been found. The first four are 6, 28, 496, and 8128.The largest containing more than 23 million digits. Perfect numbers are still being found to this day and no one has found an odd perfect number yet. Euclid proved a formula for finding perfect numbers: If   is prime, then  is perfect. In other words, n is a number whose positive divisors sums to n.